Enzymatic hydrolysis of whole grain amaranth - Lutz, Jill (Kansas State University, 2014)
There is evolving evidence that intake of whole grains protects against development of chronic diseases. Increasing the appeal of whole grain products proves difficult as they often have poor organoleptic properties attributed to the high water holding capacity, viscosity, and insolubility of components of the bran. Amaranth is a promising grain that is naturally gluten-free and has received much attention in recent years because of its excellent nutritional profile. Studies have shown encouraging approaches to modify the molecular makeup of amaranth by enzymatic hydrolysis. This approach suggests an increase in processability and incorporation of whole grain amaranth into processed foods by ameliorating the challenges inherent in the use of whole grain flours, thereby expanding consumer acceptance and intake of whole grains. This research investigates the effects of a two-level factorial design on the enzymatic hydrolysis of whole grain amaranth with enzymes alpha-amylase, cellulase, xylanase, and protease maintaining constant pH of 6 and temperature, 50°C. The main effects show decreased viscosity and water holding capacity, and increased solubility of whole grain amaranth. The most notable findings show enzymatic treatment decreases viscosity, with alpha-amylase having the most significant impact (P < 0.0001) 21,363-59± 244 cPs. Protease was eliminated from further testing as bitterness was generated with its hydrolysate. To solubilize insoluble components, a second two-level factorial design was employed analyzing pH (4.5 and 7.5) and temperature (50°C-70°C) with the same enzyme dosage as the first design. The main effects of the second design revealed alkaline conditions significantly increase soluble fiber (P < 0.0001) 3.01-5.05% ± 0.3%. Subsequent investigation proposes a response surface design with alpha-amylase in optimizing the effects of reaction time and alkaline conditions.
Keywords: Amaranth; Whole grain; Hydrolysis; Food Science (0359)